Recycling Al-Si Alloy by Semisolid Material Dragged During Continuous-Casting Strip Processing - Filho, Antonio de Pádua Lima [UNESP]; Ferreira, Lucas Veronez Goulart [UNESP]; Neto, Pedro Barbosa de Oliveira [UNESP]; Hoisand, Fabian; de Oliveira, Rodrigo Alessandro Nunes [UNESP]; Yamakami, Wyser José [UNESP]; Bazani, Marcio Antonio [UNESP]; Borodiak, Miguel (Trans Tech Publications, 2022)
Recycled Al–Si (9.2%) alloy contaminated with Fe (0.3%), Pb (3.1%) and Sn (11.4 %) was cast and poured at 650 ºC, approximately 50 ºC above the liquidus line. A cooling slope was used to obtain a semisolid material that feeds a ceramic nozzle designed to function as a good contact area for solidification and improve the quality of strip casting. The internally cooled material rolls in soluble oil (1 oil / 9 water) at a rate of 0.2 l/s and works as a heat exchanger which drags the metallic slurry puddle generated at the roll surface at a speed of 0.12 m/s. This forms a metallic strip with a thickness of 2 mm and a width varying from approximately 45 mm to 60 mm. The cooling system of the rolls, combined with four springs placed at the housing screw, prevented adhering of the metallic strip during production at a pressure of approximately 450 N. Cracks were observed on the strip surfaces; however, these defects did not interrupt the continuous flow of the solidified strip during manufacturing. The strip’s poor surface quality could be related to the Pb and Sn contamination as well as cold cracks due to the low pouring temperature. Al-Si eutectics positioned at a grain boundary of α-Al globular structures, as well as the presence of a Sn phase, resulted in a metallic strip with a yield stress, maximum stress and elongation of 94.5 MPa, 100.2 MPa and 1.6%, respectively.
Keywords: Rapid solidification; Recycling of Al-Si alloys; Rheorolling